STUDI EKSPLANATORI DAN KONFIRMATORI TENTANG KOMPETENSI TENAGA PENDIDIK BERDASARKAN INJIL YOHANES DI KALANGAN DOSEN UNIVERSITAS PGRI SEMARANG (EXPLANATORY AND CONFIRMATORY STUDY ON EDUCATOR POWER COMPETENCY BASED ON THE GOSPEL OF JOHN FOR LECTURERS) - Adhi Kusmantoro; Muner Daliman; Ragil Kristiawan; Gidion Gidion (QUAERENS: Journal of Theology and Christianity Studies, 2020)
The location of the lecturer competency research was carried out at the PGRI University of Semarang. Based on preliminary research observations there has been a decrease in lecturer competence. Therefore the aim of this research is to determine the most dominant competence, the level of competence implementation between Christian and non-Christian lecturers, and the most dominant level of functional positions. This research uses quantitative research methods. From the results of data analysis carried out with Confidence Interval at the 5% significance level, the lower bound and upper bound values ​​were obtained in the medium category so that they were in accordance with the first hypothesis. From the results of the analysis using linear regression, the personality competency dimension (D3) has about 42%. These results indicate that pedagogical competence is the most dominant dimension because it is closely related as a competent teaching staff in teacher colleges. The level of implementation of Christian lecturers and non-Christian lecturers is in the medium category. But with the analysis of the score acquisition, the score for the implementation of Christian lecturers' competence was higher, namely 99.10%. Based on the results of the analysis using Linear Regression and Binary segmentation on the fourth hypothesis Head Lector becomes the most dominant functional background category category, being able to improve 0.637 times. Efforts or policies need to be made to improve the quality of lecturers. Lokasi penelitian kompetensi dosen dilaksanakan di Universitas PGRI Semarang. Berdasarkan observasi awal penelitian telah terjadi penurunan kompetensi dosen. Oleh karena itu tujuan dalam penelitian ini adalah untuk mengetahui kompetensi yang paling dominan, tingkat implementasi kompetensi antara dosen Kristen dan dosen non-Kristen, dan tingkat jabatan fungsional yang paling dominan. Penelitian ini menggunakan metode penelitian kuantitatif. Dari hasil analisis data yang dilakukan dengan Confidence Interval pada taraf signifikansi 5% dihasilkan nilai lower Bound dan upper Bound pada kategori sedang sehingga sesuai dengan hipotesis pertama. Dari hasil analisis menggunakan regresi linier dimensi kompetensi kepribadian (D3) memiliki sebesar 42 %. Hasil tersebut menunjukkan bahwa kompetensi pedagogik sebagai dimensi yang paling dominan karena berkaitan erat sebagai tenaga pengajar yang kompeten pada perguruan tinggi keguruan. Tingkat implementasi dosen Kristen dan dosen non-Kristen pada kategori sedang. Tetapi dengan analisa perolehan skor, skor implementasi kompetensi dosen Kristen lebih tinggi yaitu 99,10%. Berdasarkan hasil analisis menggunakan Regresi linier dan Biner segmentation pada hipotesis keempat Lektor Kepala menjadi kategori latar belakang jabatan fungsional paling dominan, mampu memperbaiki sebesar 0,637 kali. Perlu dilakukan upaya atau kebijakan untuk meningkatkan kualitas dosen.